Inflation expectations and survey design - Junichi Kikuchi (Osaka University, Institute of Social and Economic Research (ISER), 2022)
We examine whether inflation expectations obtained by open- and closed-ended questions lead to different inflation expectations through a randomized controlled trial. We find that different questionnaires measure significantly different inflation expectations, especially in the short term. We further investigate whether inflation expectations induce consumers to change the intertemporal allocation of consumption via the consumption Euler equation. Our results suggest that actual expenditures are significantly responsive to inflation expectations. The EIS of the sample in the closed-ended questionnaire was higher than that of the open-ended questionnaire.
Keywords: D84; E31; 330; inflation expectations; measurement; forecast data survey data; survey design